Adverse Reactions to Antipsychotics in Parkinson Disease. Issue 3 (May 2015) - Lertxundi, Unax; Ruiz, Arantxazu Isla; Aspiazu, María Ángeles Solinís; Domingo-Echaburu, Saioa; García, Montserrat; Aguirre, Carmelo; García-Moncó, Juan Carlos
<x xml:space="preserve">Abstract</x> Purpose Although antipsychotics are well known for causing a plethora of adverse drug reactions (ADRs), the main concern when used to treat psychosis in Parkinson disease (PD) has traditionally been motor function worsening. The limited number of patients included in clinical trials contributes to underreport less common ADR. The aims of this study were to describe ADR to antipsychotics occurring in patients with PD notified to the Spanish Pharmacovigilance System and to contrast them with published reports. Methods All notifications from the Spanish Pharmacovigilance System for the last 30 years (1984-2014) where an antipsychotic was considered suspicious of the ADR in patients who were also on dopaminergic therapy were reviewed. In addition, a systematic search of MEDLINE (1966-2014) was conducted with the following Medical Subject Headings (MeSH) terms: "Parkinson disease" and "antipsychotic agents" or "psychotic disorders" and "drug-related side effects" or "adverse reactions." Results Forty-four notifications were selected for evaluation. Quetiapine was the most frequently implicated drug since 2002, and previously clozapine was the drug implied in higher number of notifications. The most severe ADR was neuroleptic malignant syndrome, which was described in 5 patients (3 cases related to quetiapine, one to haloperidol, and another to olanzapine). Conclusions Some previously unreported ADRs caused by antipsychotic drugs in patients with PD have been described for the first time in this study, although there are in general well-known antipsychotic adverse effects. It is remarkable that some notifications involve the use of drugs not recommended in these patients.